Coated and uncoated reinforcements metal matrix composites characteristics and applications – A critical review. Issue 1 (1st January 2020) - B M, Karthik; M C, Gowrishankar; Sharma, Sathyashankara; Hiremath, Pavan; Shettar, Manjunath; Shetty, Nagaraj
Abstract: Nowadays, metal matrix composites are being comprehensively used in aero and automotive applications. The usage of composites increased because of their impressive properties viz., improved strength, impact resistance, and tailored features. Compared to uncoated, coated reinforcements in the matrix improves wettability with thinner grain boundary, grain fineness, and the ability for secondary hardening. Improvement in thermal expansion and conductivity makes the composite suitable for moderate temperature shock resistance is the new openings in the field. Conventional liquid stir casting, Rheo-process, and Diffusion roll bonding are some of the methods employed for the processing of composites. Hybridisation of reinforcements with at least one as coated in the matrix improves solid solution strengthening of composites, hence responsible for improved strength and bulk hardness. Generally, a critical literature survey points to copper and nickel coatings. Copper coating rises microhardness, shows poor EMI shielding effectiveness compared to nickel-coated, whereas, nickel-coated reinforcement composites show excellent corrosion resistance compared to that of copper-coated reinforcement. Cobalt-coated nanoparticles reinforced composites upsurges compressive strength and tribological properties compared to nickel-coated ones. However, the extensive review work undertaken collects the possibilities of using different reinforcements in bare state and coated state with or without hybridisation. A comparison of data with property analysis will open the way for further research activities with hybridisation of both or single-coated reinforcements in the matrix and may help to prepare the standard guidelines to advance with a statistical approach. The objective of the present work is to collect the data on the aluminium matrix composites with different reinforcements in coated as well as bare forms and dig on the possibilities for property enhancement.